Transcriptional Response of Polycomb Group Genes to Status Epilepticus in Mice is Modified by Prior Exposure to Epileptic Preconditioning - Reynolds, James P.; Miller-Delaney, Suzanne F. C.; Jimenez-Mateos, Eva M.; Sano, Takanori; McKiernan, Ross C.; Simon, Roger P.; Henshall, David C. (Frontiers in Neurology, 2015)
Exposure of the brain to brief, non-harmful seizures can activate protective mechanisms that temporarily generate a damage-refractory state. This process, termed epileptic tolerance, is associated with large-scale down-regulation of gene expression. Polycomb group proteins are master controllers of gene silencing during development that are re-activated by injury to the brain. Here we explored the transcriptional response of genes associated with polycomb repressor complex (PRC) 1 (Ring1A and Ring1B and Bmi1) and PRC2 (Ezh1, Ezh2 and Suz12), as well as additional transcriptional regulators Sirt1, Yy1 and Yy2, in a mouse model of status epilepticus. Findings were contrasted to changes after status epilepticus in mice previously given brief seizures to evoke tolerance. Real-time quantitative PCR showed status epilepticus prompted an early (1 h) increase in expression of several genes in PRC1 and PRC2 in the hippocampus, followed by down-regulation of many of the same genes at later times points (4 , 8 and 24 h). Spatio-temporal differences were found among PRC2 genes in epileptic tolerance, including increased expression of Ezh2, Suz12 and Yy2 relative to the normal injury response to status epilepticus. In contrast, PRC1 complex genes including Ring 1B and Bmi1 displayed differential down-regulation in epileptic tolerance. The present study characterizes polycomb group gene expression following status epilepticus and shows prior seizure exposure produces select changes to PRC1 and PRC2 composition that may influence differential gene expression in epileptic tolerance.